Mass media management : technological backgrounds - Gazenko, Roman (Array, 2018)
The paper provides a professional overview of the development of media technology, as well as the influence of technology on media content and its interpretation. The aim of communication is definitively to connect the source with the receiver. It means to solve the main problem – to overwhelm the obstacle of space and time. Technological goals since the dark ages were aimed at increasing the physical features of man as direct carrier or to replace him by a more efficient one.